THE IMPLEMENTATION OF POE (PREDICT OBSERVE EXPLAIN) MODEL TO IMPROVE STUDENT’S CONCEPT UNDERSTANDING ON NEWTON’S LAW - Haris Rosdianto; Eka Murdani; Hendra . (Jurnal Pendidikan Fisika, 2017)
The aim of this study is to determine the improvement of student’s concept understanding on Newton's Law with the implementation of POE learning model. This research type is quantitative and using pre-experiment method with one group pre-test post-test design. In this study, the measurements in the form of pre-test to the subject and then treated with the POE learning model and within a certain time post-test is given. The population in this research is all students of class VIII in SMP 5 Singkawang city. The sample of the research is the students of class VIII E which amounted to 20 people and the sampling technique using purposive sampling. The result of data analysis using N-gain equation shows improvement of student’s concept understanding by 0,64 with medium category.